Development of Aroma Massage Oil for Relieving Muscle Pain and Satisfaction Evaluation in Humans - Tapanee Hongratanaworakit, Sukanya Soontornmanokul, Phattarapond Wongareesanti (Journal of Applied Pharmaceutical Science, 2018)
The objective of this study was to develop aroma massage oil containing natural oils for relieving muscle pain and evaluate users’ satisfaction. In addition, the skin irritation and skin sensitization of products were tested by using the Kligman maximization method. Seven essential oils were used as an active ingredient in the formula. Six carrier oils were used as a carrier oil in the formula. Tests of odor preference and odor acceptance of products were investigated in sixty-one consumers. The products were evaluated the preliminary physical stability in terms of color, smell, rancidity, viscosity, and precipitation, for a period of eight weeks. In addition, thirty consumers participated in the satisfaction evaluation. The results showed that consumers gave the most preference and acceptance to a blended essential oil preparation 1 (BEOP1) which composed of rosemary, lavender, patchouli, eucalyptus, and peppermint oils. The consumers gave an overall satisfied with carrier oil formulas which consisted of sweet almond, grape seed, avocado, jojoba oils, and macadamia oils. A massage oil formula which composed of BEOP1, vitamin E acetate, isopropyl myristate, and carrier oils gave the best physical characteristics. Moreover, developed massage oil remained stable for 8 weeks. No skin irritation and no skin sensitization were observed after volunteers applied to developed massage oil on the inner forearm for two weeks. Therefore, it could be suggested that developed massage oil was safety.
Keywords: Aromatherapy massage oil, muscle pain, odor preference, odor acceptance, irritation, sensitization.